Frequency Reconfigurable Antenna Using SSRR Metamaterial for Smart Applications - Dwivedi S. (My University, 2025)
In order to use an antenna at different frequencies in a particular frequency band, a Frequency Reconfigurable Antenna design is proposed using Single Split Ring Resonators (SSRR). It uses a FR4(2.5×2.5mm2) as a substrate with a thickness of 0.25 mm. It uses an inset feed and a metal surface at the back of substrate of same size which act as a reflector. This reflector is used to increase the gain and other characteristics of the antenna. Single PIN diode is used as switch for connecting the Split Ring Resonators. By ON/OFF the switch we get the two different modes and different resonating frequencies at those modes. It exhibits the VSWR <2 and simulated on CSToMWSo. It resonates at two different frequencies, 10.9 GHz, 9.2 GHz, with a maximum gain of 8.45 dBi, 8.54dBi respectively. © 2023 IEEE.